Effect of Various Development Periods on Accumulation of Some Mineral Elements on the Leaves of Strawberry Cultivars (Fragaria X ananassa Dutch. L) - YILMAZ, HUDAI; MURADOGLU, FERHAT; YILDIZ, KENAN (Asian Journal of Chemistry, 2010)
An experiment has been set up with Tudla, Muir, Douglas, Rupella, Moraline, Evita, Aiko, Northeastern, Tioga, Elvira and Delmarvel cultivars for mineral accumulations of nitrogen, phosphorus, potassium, calcium, magnesium, manganese, zinc, copper, iron and boron on plants' leaves were analyzed in three different periods which are fruit formation (May 26th), stolon formation (July 13th) and beginning of resting period (September 27th). It was determined that generally mineral elements accumulation change in relation to development periods. In addition, the periodic change in nitrogen, potassium, manganese, zinc, copper and boron minerals were more evident. No clear change was seen in phosphorus and calcium. Despite that changes were seen in iron mineral at the cultivar level, this situation did not present itself in general averages. When every cultivar is analyzed by itself, there were clear differences among cultivars. Every cultivar's mineral element accumulation level has shown variation. Differences among cultivars' averages have been found statistically significant.